Effect of the COVID-19 pandemic and subsequent social distancing on individual's mental health - Abdulkareem Salih, Sarah; Ismail, Sumarni; Najm, Ahmed; Ismail, Nurhilmiyani (Universiti Putra Malaysia Press, 2023)
The COVID-19 coronavirus, an infectious disease originating in Wuhan, has become an outbreak worldwide, leading to unprecedented measures restricting social and physical activities in many countries. The subsequent social distancing of COVID-19 has significantly resulted in many psychological consequences. The current study examines the impact of social distancing during the COVID-19 pandemic on the mental health symptoms of Selangor State, Malaysia residents. An online survey was conducted through social media platforms targeting residents of Selangor State in Malaysia. A convenience sampling method was led to include 258 respondents in the study. The questionnaire on the symptoms of mental health related to fear of COVID-19 included 13 items developed from the existing studies. The results showed that symptoms of mental health problems related to fear of COVID-19 are negatively associated with the likelihood of social interaction. The overall score of symptoms of mental health related to the fear of COVID-19 showed moderate symptoms of mental problems related to the fear of COVID-19. The factor of age was also associated with higher symptomatology of mental health problems related to fear of COVID-19. Thus, related measures and guidelines must consider the mental well-being of the at-risk person as the pandemic continues. The current study’s findings contribute to the knowledge gaps in behavioural health during biological disasters. It also provides a reference for professionals and policymakers to develop programs and measures to handle the psychosocial status of the affected people.